(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This study investigates the impact of storms across offshore wind assets listed in the ScotWind leasing round (as of December 2023) by looking at how the frequency and intensity of storms have changed in the last ten years and identifying which assets are most vulnerable. Assessing the risk posed by hazards such as storms to offshore energy infrastructure is critical to meeting ambitious net zero targets set by both the UK and Scottish governments. This analysis uses GIS as a method of exploring ERA5 reanalysis data to assess the occurrence of both wind speeds and wave heights ranked ten or above on the Beaufort Scale at 52 key locations across Scotland between 2014 and 2023. While several northern assets are identified as particularly vulnerable to these forms of extreme weather, no significant pattern of change has been observed in the frequency or intensity of storms.